Adhesive layer resin composition, glued copper foil and application thereof
By using a specific combination of adhesive layer resin composition in high-frequency hydrocarbon products, the problems of unstable anti-peel resistance and insufficient flow glue are solved, and efficient preparation of glue-coated copper foil is achieved, which improves the peel strength and heat resistance of the product.
Patent Information
- Application Number
- CN202411870206.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
AI Technical Summary
The existing high-frequency hydrocarbon system products have instability and insufficient flow glue in terms of peel resistance, which leads to the fact that thin sheets are prone to failure to peel resistance in large-scale production, increasing production costs and quality risks.
A binder layer resin composition was developed to prepare a glue-coated copper foil with good fluidity and stable peel strength by combining SBS with an unsaturated double bond with a number average molecular weight of 12000-25000 g/mol and polybutadiene with an unsaturated double bond with a number average molecular weight of ≤5000 g/mol, combined with a free radical initiator.
It realizes the stable low dielectric constant, low dielectric loss and stable anti-peeling performance of glue-coated copper foil, improves the peel strength and heat resistance of hydrocarbon products, and is suitable for processing of high-frequency hydrocarbon products.
Smart Images

Figure BDA0005195560780000101 
Figure BDA0005195560780000121 
Figure BDA0005195560780000122
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic materials and relates to an adhesive layer resin composition, a glue-coated copper foil and applications thereof. Background Art
[0002] Among the existing printed circuit board materials, high-frequency hydrocarbon system products are widely used in the development of electronic products such as radars, antennas, and power amplifiers due to their excellent dielectric properties and low prices. High-frequency hydrocarbon products usually have two characteristics. One is that they are prepared using non-polar low dielectric loss resins. This type of resin has weak bonding properties, so the peel strength of copper foil of hydrocarbon products is often poor. The other is that a high filler ratio is used to adjust the dielectric constant, viscosity, heat resistance, and flame retardancy. The high filler ratio reduces the overall flow of hydrocarbon products.
[0003] There are usually two ways to improve the peel strength of high-frequency hydrocarbon system products. One is to use high-roughness copper foil to improve the peel resistance by increasing the contact area between the copper teeth and the substrate. The other is to use adhesive-coated copper foil, which is a layer of adhesive with high peel strength applied on the copper foil to improve the bonding strength between the copper foil and the hydrocarbon substrate. Since the adhesive layer itself has high peel resistance, the roughness requirement for the copper foil is relatively low, which can solve the bonding problem between low-roughness copper foil and the hydrocarbon substrate.
[0004] The inventors found that in the former method, when using high-roughness copper foil, the peeling resistance and glue flow of hydrocarbon products are strongly correlated, and the peeling resistance stability of hydrocarbon products is often related to glue flow. There are many factors that can lead to low peeling resistance of hydrocarbon products, such as less pressing matching. When only one or two adhesive sheets are used to press thin plates, the glue squeezed out of the adhesive sheet is small, and the resin does not wet the copper foil well, resulting in low peeling resistance; for example, the steel plate is uneven, partially under-pressed, and less glue is squeezed out, resulting in low peeling resistance. Among hydrocarbon products, the peeling resistance of thin plates has always been an indicator with relatively high risks. Only when the glue squeezed out of the adhesive sheet evenly and fully infiltrates the copper foil, the peeling resistance of the product will be stable. However, the glue flow of hydrocarbon products is not the larger the better. Excessive glue flow will cause the problem of board edge grooves. Board edge grooves are a phenomenon in which the resin at the edge of the board gathers and flows in a dendritic manner to form an apparent defect.
[0005] In the formulation design of hydrocarbon products, there needs to be a certain amount of glue flow, but not too much glue flow. The glue flow needs of thick boards are met, but the balance achieved in the compromise cannot fully resist the fluctuation of anti-peeling caused by process instability. Especially for thin boards below 0.3mm, in actual large-scale production, due to various process factors, the anti-peeling is unqualified, resulting in certain scrap losses or a high risk of customer complaints after entering the circuit board factory.
[0006] The latter method, i.e. the technology of coated copper foil, can improve the peel resistance more than the use of high-roughness copper foil, raising the peel resistance to a safety threshold of more than 1.0N / mm, and can use low-profile copper foil to improve insertion loss. However, since hydrocarbon resins often do not have high peel strength, the current high-frequency hydrocarbon coated copper foil technology often cannot use hydrocarbon resin as the main body, but needs to add various components to improve peel resistance to the adhesive layer, and introduce resins containing polar groups such as acrylate, maleic anhydride, and epoxy groups. Therefore, there are large differences in the components of the adhesive layer of the coated copper foil and the hydrocarbon substrate, and there are certain differences in reaction rate, curing temperature, and electrical properties. Since hydrocarbon substrates often require high temperature and high pressure to fully crosslink and cure their dense double bonds, the adhesive layer of the copper foil has already begun to cure, but the hydrocarbon substrate is only in the initial curing stage, so that the crosslinking of the two is not sufficient. When the application environment is harsh, the combination of the adhesive layer of the copper foil and the hydrocarbon substrate will have the risk of stratification. In the applications of some customers, it is found that this solution will result in good bonding between the adhesive layer of the copper foil and the copper foil, but stratification with the substrate. In terms of electrical properties, the adhesive layer of the copper foil also has certain shortcomings. Although its impact on electrical properties can be reduced by coating as thinly as possible, for some hydrocarbon products that require thin specifications, such as plates with a thickness of less than 0.3mm, the adhesive layer of the copper foil still occupies a relatively large volume proportion, which has a significant impact on electrical properties.
[0007] CN113072885B discloses an adhesive resin composition, which uses unmodified polyarylether as the main body to improve the heat resistance of the resin composition, and adds unsaturated metal salts to improve the adhesion of the resin composition, so that it can meet the requirements of high peel strength after high temperature and long-term curing. However, it has a small content of unsaturated double bonds and a fast reaction rate, which is quite different from the curing window of hydrocarbon system substrates, resulting in low crosslinking density between the adhesive layer and the substrate, and a certain attenuation of anti-peeling under thermal shock.
[0008] In view of the above situation, it is a feasible solution to develop a coated copper foil with improved peeling resistance using hydrocarbon resin as the main body. In most hydrocarbon series products, polybutadiene, which is cheap, has excellent electrical properties and good fluidity, is selected as the main body. However, if only polybutadiene is used as the main body, the coated copper foil will be sticky, and the production process will stick to the roller and cannot be rolled up.
[0009] CN101157788 discloses a hydrocarbon resin composition, which adds a relatively high proportion of polybutadiene to the formula, and introduces a low-temperature initiator with a very short half-life to partially solidify the polybutadiene resin during the baking stage, thereby improving the phase separation problem of polybutadiene and greatly reducing its viscosity, thereby meeting the requirements of the production of stacking ingredients. However, after the polybutadiene is partially solidified, the molecular weight increases sharply, the fluidity of the system decreases significantly, and it is easy to cause poor wetting and the presence of cavities between the bonding sheet and the copper teeth.
[0010] CN202111679705 discloses a coated copper foil resin composition, which is a combination of high molecular weight polybutadiene with a molecular weight of 120,000-300,000 and low molecular weight polybutadiene, which reduces the overall viscosity of the resin. However, the high molecular weight polybutadiene also inhibits the flow of the resin. In the application of thin-gauge hydrocarbon sheets with less glue flow, the substrate may not be able to squeeze out the glue and cannot be tightly bonded.
[0011] The inventors found that when using high-roughness copper foil to improve anti-peeling, the level and stability of anti-peeling does not depend on the adhesive force of the resin, but more on whether the resin in the adhesive sheet is squeezed out and fully wets the copper foil. Therefore, the purpose of the present invention is to develop a coated copper foil with good fluidity, which can fully wet the copper foil and the substrate, has the same electrical properties as the hydrocarbon substrate, and has the same reactivity and curing temperature as the hydrocarbon substrate, and has a thickness of less than or equal to 6μm.
[0012] In the production process of hydrocarbon products, most high-frequency hydrocarbon sheets with large anti-peel fluctuations or unqualified have the common problem of small glue flow. The glue flow of hydrocarbon substrates is different from that of most FR-4 products. Due to its high filler content, it usually has little fluidity as a whole. Under high temperature and high pressure, the resin melts and is squeezed out of the filler by pressure, wetting the copper foil, and forming a very thin cream layer between the copper foil and the substrate, thereby producing anti-peeling. Since high-frequency hydrocarbon products often have multiple thickness specifications, in order to prevent the thick-specification hydrocarbon sheets from having excessive glue flow and forming gullies, the glue flow is often designed to be relatively small. This results in thin-specification hydrocarbon sheets often having large anti-peel fluctuations due to small glue flow. In order to solve the problem of different glue flows required for thick and thin sheets, a resin bonding layer with good fluidity and non-stickiness should be developed to improve the anti-peeling performance of some thin-specification products. Summary of the invention
[0013] In view of the shortcomings of the prior art, the object of the present invention is to provide an adhesive layer resin composition, a coated copper foil and applications thereof. The adhesive layer resin composition of the present invention has good fluidity and can fully wet the copper foil and the substrate, so that the coated copper foil has a stable low dielectric constant, low dielectric loss and stable anti-stripping performance.
[0014] To achieve this object, the present invention adopts the following technical solutions:
[0015] In one aspect, the present invention provides an adhesive layer resin composition, wherein the adhesive layer resin composition is composed of the following components in parts by weight:
[0016] (A) 65-90 parts of SBS with unsaturated double bonds having a number average molecular weight Mn of 12000-25000 g / mol;
[0017] (B) 10-35 parts of polybutadiene with unsaturated double bonds and a number average molecular weight Mn≤5000 g / mol;
[0018] (C) Free radical initiator.
[0019] In the present invention, the inventors found that the component (A) SBS, when its number average molecular weight is 12000-25000 g / mol, has a low softening point, can improve the stickiness of the pure hydrocarbon resin system adhesive layer at room temperature, and still has a certain fluidity during the lamination and curing glue flow stage, and the prepared adhesive layer can fully wet the substrate and copper foil. When its number average molecular weight is lower than 12000 g / mol, the viscosity of the adhesive layer increases, the operability deteriorates, and the glue flow is too large, and it is easy to produce grooves due to excessive glue flow when pressed with the hydrocarbon substrate; when its number average molecular weight is higher than 25000 g / mol, its fluidity decreases, the wetting of the hydrocarbon substrate and copper foil is poor, and the anti-peeling is unstable.
[0020] In the present invention, the number average molecular weight Mn of the SBS of component (A) is 12000-25000 g / mol, for example: 12000 g / mol, 14000 g / mol, 17000 g / mol, 19000 g / mol, 20000 g / mol, 22000 g / mol, 25000 g / mol, etc.
[0021] Preferably, the SBS has unsaturated double bonds, which can crosslink and solidify with the hydrocarbon substrate, thereby increasing the bonding strength between the adhesive layer and the hydrocarbon substrate and improving the stability of the PS under thermal shock. The inventors found that hydrogenated SBS has better electrical properties but poor heat resistance.
[0022] Preferably, the SBS molecules with unsaturated double bonds contain 40% to 60% (e.g., 40%, 43%, 45%, 48%, 50%, 53%, 55%, 58% or 60%) of butadiene structure in a molar ratio, and the molar ratio of butadiene added at the 1,2 positions in the butadiene molecular structure is ≥80% (e.g., 80%, 83%, 85%, 88%, 90%, 93%, 95%, 98%, etc.), ensuring that the adhesive layer has a relatively high cross-linking density and has a relatively good riveting effect with the copper foil and copper teeth with high roughness, thereby improving the peel strength of the substrate.
[0023] Preferably, the component (A) is selected from any one of a styrene-butadiene diblock copolymer, a styrene-butadiene-styrene triblock copolymer, a styrene-(ethylene-butylene)-styrene triblock copolymer, a styrene-isoprene diblock copolymer, a styrene-isoprene-styrene triblock copolymer, a styrene-(ethylene-propylene)-styrene triblock copolymer or a styrene-(ethylene-butylene) diblock copolymer or a mixture of at least two thereof.
[0024] The inventors have found that the polybutadiene with unsaturated double bonds and a number average molecular weight Mn≤5000 g / mol of the component (B) can improve the wettability and crosslinking density of the adhesive layer, and improve the peel strength and heat resistance.
[0025] In the present invention, the number average molecular weight Mn of the polybutadiene component with unsaturated double bonds of component (B) is ≤5000 g / mol, for example: 1200 g / mol, 2200 g / mol, 3600 g / mol, 4100 g / mol, 5000 g / mol, etc.
[0026] In the present invention, the weight ratio of butadiene added at the 1,2-position in the polybutadiene molecules with unsaturated double bonds of component (B) with a number average molecular weight Mn≤5000 g / mol is greater than or equal to 65%, such as 65%, 74%, 81%, 93% or 96%, etc. If the weight ratio of butadiene added at the 1,2-position is less than 65%, the crosslinking density of the system is too low, the heat resistance is insufficient, and the use requirements cannot be met.
[0027] In the present invention, since the adhesive layer is very thin, if the number average molecular weight of the polybutadiene with unsaturated double bonds with a number average molecular weight Mn≤5000g / mol is too large, the fluidity of the adhesive layer will be insufficient, and it will not be able to fully wet the surface of the hydrocarbon substrate and the copper teeth during lamination to improve the peel strength; if the weight ratio of butadiene added at the 1,2-position in the polybutadiene molecules with unsaturated double bonds with a number average molecular weight Mn≤5000g / mol is too low, the cross-linking density after curing will be small, resulting in insufficient heat resistance.
[0028] Specific examples of commercially available polybutadiene having unsaturated double bonds and having a number average molecular weight of Mn≤5000 g / mol include B1000, B2000, and B3000 manufactured by Nippon Soda Co., Ltd. and Ricon 152 and Ricon 154 manufactured by Cray Valley Co., Ltd., USA, but are not limited to the above.
[0029] The molecular weight test method in the present invention is GB / T 21863-2008, including number average molecular weight and weight average molecular weight, as measured by gel permeation chromatography based on polystyrene calibration.
[0030] In the adhesive layer resin composition of the present invention, the amount of SBS with unsaturated double bonds having a number average molecular weight Mn of 15000-25000 g / mol can be 65 parts, 68 parts, 70 parts, 73 parts, 75 parts, 78 parts, 80 parts, 83 parts, 85 parts, 88 parts or 90 parts. The inventors found that if the amount is less than 65 parts, the viscosity of the adhesive layer is too high, and the adhesive-coated copper foil cannot be torn apart after rolling. If the amount is more than 90 parts, the cross-linking density is too low, the heat resistance is insufficient after curing, and it is easy to delaminate and explode when heated.
[0031] In the adhesive layer resin composition of the present invention, the amount of the polybutadiene with unsaturated double bonds of component (B) with a number average molecular weight Mn≤5000g / mol can be 10 parts, 13 parts, 15 parts, 18 parts, 20 parts, 23 parts, 25 parts, 28 parts, 30 parts, 33 parts or 35 parts. The inventors found that when the amount exceeds 35 parts, the viscosity of the adhesive layer is too high, and the adhesive-coated copper foil is difficult to stack normally. When the amount is less than 10 parts, the fluidity of the adhesive layer is poor, and it is difficult to fully wet the hydrocarbon substrate and the copper teeth during the pressing, resulting in unstable anti-peeling, and the cross-linking density of the adhesive layer after curing is low, and the heat resistance is poor.
[0032] The adhesive layer of the present invention further comprises a free radical initiator, and the free radical initiator is selected from one or a mixture of at least two of an organic peroxide free radical initiator or a carbon-based free radical initiator.
[0033] Preferably, the organic peroxide free radical initiator is selected from di-tert-butyl peroxide, dilauroyl peroxide, dibenzoyl peroxide, isopropyl peroxyneodecanoate, t-pentyl peroxypivalate, t-butyl peroxypivalate, t-butyl peroxyisobutyrate, t-butyl peroxy-3,5,5-trimethylhexanoate, t-butyl peroxybenzoate, 1,1-di-tert-butyl peroxy-3,5,5-trimethylcyclohexane, 1,1-di-tert-butyl peroxycyclohexane, 2,2-di(tert-butylperoxy)butane, bis(4-tert-butylcyclohexane)-1,2-di-tert-butylperoxy)butane, t-butyl peroxy-3,5,5-trimethylhexanoate, t-butyl peroxybenzoate, t-butyl peroxy-3,5,5-trimethylcyclohexane, t-butyl peroxy-1,2-di-tert-butylper ... The invention can be selected from the group consisting of one or a mixture of at least two of 2,4-di(tert-butylperoxy)pentyl peroxide, 2,6-di(tert-butylperoxy)pentyl peroxide, 2,4-di(tert-butylperoxy)pentyl peroxide, 2,6-di(tert-butylperoxy)pentyl peroxide, 2,5-dimethyl-2,5-di-tert-butylperoxyisopropyl peroxide, 2,5-dimethyl-2,5-di-tert-butylperoxyisopropyl peroxide, diisopropylbenzene hydroperoxide, 2-ethylhexyl tert-butylperoxycarbonate, n-butyl 4,4-di(tert-butylperoxy)pentyl ester, methyl ethyl ketone peroxide and cyclohexane peroxide.
[0034] Preferably, the carbon-based free radical initiator is selected from one of 2,3-dimethyl-2,3-diphenylbutane, 2,3-dimethyl-2,3-di(4-methylphenyl)butane, 2,3-dimethyl-2,3-di(4-isopropylphenyl)butane, and 3,4-dimethyl-3,4-diphenylhexane, or a mixture of at least two thereof.
[0035] In the present invention, based on 100 parts by weight of components (A) + (B), the amount of the initiator is 0.1-5 parts by weight, for example, 0.4 parts, 1.2 parts, 1.9 parts, 2.5 parts, 3.3 parts, 4.1 parts, 4.8 parts, etc.
[0036] On the other hand, the present invention provides a rubber-coated copper foil, comprising a copper foil layer and an adhesive layer coated on the surface of the copper foil layer, wherein the adhesive layer is prepared from the adhesive layer resin composition as described above.
[0037] The present invention designs the specific composition of the adhesive layer to prepare a resin composition with excellent performance, and further prepares a coated copper foil with good fluidity, stable peel strength, excellent dielectric properties and heat resistance, which is suitable for high-frequency hydrocarbon product processing.
[0038] Preferably, the thickness of the adhesive layer is 3-6 μm, for example, 3 μm, 4 μm, 5 μm, 5.5 μm or 7 μm. The inventors found that when the adhesive layer thickness of the adhesive-coated copper foil is less than 3 μm, the adhesive content of the adhesive layer is insufficient, the wetting of the substrate and the copper teeth is incomplete, and the anti-peeling performance fluctuates. When the adhesive layer thickness of the adhesive-coated copper foil is greater than 7 μm, although the wetting of the substrate and the copper teeth is more sufficient, when the thickness of the plate is less than 0.3 mm, the dielectric constant will be lowered.
[0039] In the present invention, the adhesive layer is coated on the matte surface of the copper foil.
[0040] Preferably, the Rz of the rough surface of the copper foil is ≥5 μm, for example, Rz is 5 μm, 6 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, etc. The roughness test method is determined according to the contact roughness instrument method.
[0041] In the present invention, the preparation method of the adhesive-coated copper foil comprises the following steps:
[0042] The components of the adhesive layer resin composition are dissolved in a solvent, stirred evenly, and coated on the surface of the copper foil. The solvent is removed to obtain a coated copper foil with an adhesive layer.
[0043] Preferably, the solvent is selected from aromatic hydrocarbon solvents such as toluene, xylene, mesitylene, etc., or ketone solvents such as acetone, butanone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.
[0044] Preferably, the solvent is removed in a dry manner.
[0045] Preferably, the drying temperature is 90-180°C, for example, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, etc.
[0046] In another aspect, the present invention provides a copper-clad laminate comprising a hydrocarbon bonding sheet and the above-mentioned adhesive-coated copper foil coated on one side or both sides of the hydrocarbon bonding sheet.
[0047] In the present invention, the method for preparing the copper-clad laminate comprises the following steps:
[0048] Prepare one or more hydrocarbon bonding sheets, place glue-coated copper foil on both sides of the stacked hydrocarbon bonding sheets, and put them into a press for lamination to prepare a copper-clad laminate.
[0049] Preferably, the lamination process is preferably vacuum lamination, which can be achieved by a vacuum laminator. The lamination time is 60-150 min, such as 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, etc.; the lamination temperature is 240-265°C, such as 240°C, 245°C, 250°C, 255°C, 260°C, 265°C, etc.; the lamination pressure is 20-60 kg / cm 2 , for example 20kg / cm 2 , 25kg / cm 2 、30kg / cm 2 、35kg / cm 2 , 40kg / cm 2 , 45kg / cm 2 , 50kg / cm 2 、55kg / cm 2 、60kg / cm 2 wait.
[0050] The specific parameters of the lamination molding time, temperature and pressure are determined based on the hydrocarbon bonding sheet used in combination. According to the differences in different formulations, the lamination parameters can be flexibly adjusted within a limited range.
[0051] In another aspect, the present invention provides a printed circuit board, wherein the printed circuit board comprises at least one of the above-mentioned glue-coated copper foil and / or the above-mentioned copper-clad laminate.
[0052] Preferably, the printed circuit board is a high-frequency substrate.
[0053] Compared with the prior art, the present invention has the following beneficial effects:
[0054] (1) The adhesive layer resin composition provided by the present invention, when coated on a copper foil, can improve the peel strength of existing hydrocarbon products, especially hydrocarbon products with a thickness of less than 0.5 mm, by 0.2-0.3 N / mm. The formed adhesive layer is substantially the same as the hydrocarbon substrate in terms of initial reaction temperature, reaction rate, and curing temperature, can be fully cured simultaneously, and has good bonding strength with the hydrocarbon substrate, thereby improving heat resistance.
[0055] (2) The adhesive layer resin composition provided by the present invention uses a thermosetting resin with unsaturated double bonds with a number average molecular weight Mn of 12000 to 25000 g / mol as the main body. It is completely non-sticky when coated on the copper foil, which facilitates the normal winding of the RCC. The molecular weight of the coating is not high, and it is easy to flow into the adhesive sheet and merge into one after heating, fully infiltrating the copper teeth, which is equivalent to a thin cream layer. DETAILED DESCRIPTION
[0056] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0057] The materials and grades involved in the following examples and comparative examples are shown in Table 1.
[0058] Table 1
[0059]
[0060] Examples 1-6 and Comparative Examples 1-11
[0061] Examples 1-7 and Comparative Examples 1-10 provide a glue-coated copper foil and a metal foil-clad laminate, respectively. The specific composition of the adhesive layer is shown in Table 2-4 below:
[0062] The preparation methods of Examples 1-7 and Comparative Examples 2-10 are as follows:
[0063] (1) Take the materials according to the amount of each component in the formula of Table 1, dissolve them in toluene, add them into a stirring kettle, dilute them with toluene to a solid content of 60%, stir and mix them evenly, and obtain a resin glue solution.
[0064] (2) Coating the resin adhesive on the copper foil, drying the solvent to a dry state, and obtaining the adhesive-coated copper foil.
[0065] (3) A sheet of S7135 hydrocarbon adhesive sheet with a thickness of 1080 cloth and 3.33 mil was stacked with a sheet of the prepared adhesive-coated copper foil on the top and bottom, and the sheet was put into a press for curing to obtain a metal foil laminate. The curing time was 120 minutes, the curing temperature was 250°C, and the curing pressure was 50 kg / cm 2 .
[0066] The only difference between Comparative Example 1 and Example 1 is that no adhesive-coated copper foil is prepared, and the copper foil is directly pressed onto the S7135 hydrocarbon bonding sheet.
[0067] Performance Testing
[0068] The following performance tests were conducted on the above-mentioned embodiments and comparative examples of the adhesive-coated copper foil and the metal foil-clad laminate:
[0069] Adhesion of the adhesive layer of the glue-coated copper foil: Lay two adhesive layers of the glue-coated copper foil together and press them flat with a steel plate to make them overlap tightly. After about 5 minutes, remove the steel plate and tear off the copper foil to see whether the adhesive layers on both sides are stuck.
[0070] Dielectric constant (Dk) and dielectric loss tangent (Df): measured at 10 GHz using the Split Dielectric Pillar Resonator (SPDR) method as specified in IPC-TM-650 2.5.5.15.
[0071] Sheet peel strength (PS): Test the peel strength of copper foil according to the "after thermal stress" experimental conditions in IPC-TM-650 2.4.8 method, unit N / mm.
[0072] Thermal stress (baking plate method): Clamp a 300×300mm plate on a rack with a clip and bake it in an oven at 288℃ for 20 minutes. After taking it out, observe whether there is stratification and bubbling on the surface of the plate.
[0073] The above performance test results are detailed in Table 2-3 below.
[0074] Table 2
[0075]
[0076] Table 3
[0077]
[0078]
[0079] Table 4
[0080]
[0081] From the comparison between Examples 1-7 and Comparative Example 1, it can be seen that the adhesive-coated copper foil of the present invention has no stickiness, is easy to stack, can improve the peel strength of hydrocarbon substrates, and has almost no effect on the electrical properties of the sheet when applied to a single sheet of material, and has good heat resistance.
[0082] From the comparison between Examples 1-7 and Comparative Examples 2-6, it can be seen that the present invention can obtain a metal foil-clad laminate with better performance by limiting the molecular weight and 1,2-structured butadiene content of SBS with unsaturated double bonds and polybutadiene with unsaturated double bonds within specific ranges.
[0083] From the comparison between Examples 1-7 and Comparative Examples 7-10, it can be seen that the present invention can obtain a metal foil-clad laminate with better performance by limiting the amount and coating thickness of SBS with unsaturated double bonds and polybutadiene with unsaturated double bonds within a specific range.
[0084] In summary, the present invention designs the composition of the resin, uses SBS with unsaturated double bonds and low molecular weight polybutadiene in combination, and controls the dosage of the two within a specific range, thereby preparing an adhesive layer of the coated copper foil with excellent performance, and further preparing a coated copper foil with good fluidity, stable peel strength, excellent dielectric properties and heat resistance, which is suitable for high-frequency hydrocarbon product processing.
[0085] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the adhesive layer resin composition, the coated copper foil and the application thereof, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. An adhesive layer resin composition, characterized in that The adhesive layer resin composition is composed of the following components in parts by weight: (A) 65-90 parts of SBS with unsaturated double bonds having a number average molecular weight Mn of 12000-25000 g / mol; (B) 10-35 parts of polybutadiene with unsaturated double bonds and a number average molecular weight Mn≤5000 g / mol; (C) Free radical initiator.
2. The adhesive layer resin composition according to claim 1, characterized in that The SBS molecule with unsaturated double bonds contains 40% to 60% of butadiene structure by mole, and the mole content of butadiene added at the 1,2 positions in the butadiene molecular structure is ≥80%.
3. The adhesive layer resin composition according to claim 1 or 2, characterized in that The component (A) is selected from any one of styrene-butadiene diblock copolymer, styrene-butadiene-styrene triblock copolymer, styrene-(ethylene-butylene)-styrene triblock copolymer, styrene-isoprene diblock copolymer, styrene-isoprene-styrene triblock copolymer, styrene-(ethylene-propylene)-styrene triblock copolymer or styrene-(ethylene-butylene) diblock copolymer or a mixture of at least two thereof.
4. The adhesive layer resin composition according to any one of claims 1 to 3, characterized in that The weight ratio of butadiene added at the 1,2 positions in the polybutadiene molecules with unsaturated double bonds and a number average molecular weight Mn≤5000 g / mol of the component (B) is greater than or equal to 65%.
5. The adhesive layer resin composition according to any one of claims 1 to 4, characterized in that The free radical initiator is selected from one or a mixture of at least two of an organic peroxide free radical initiator or a carbon-based free radical initiator; Preferably, the organic peroxide free radical initiator is selected from di-tert-butyl peroxide, dilauroyl peroxide, dibenzoyl peroxide, isopropyl peroxyneodecanoate, t-pentyl peroxypivalate, t-butyl peroxypivalate, t-butyl peroxyisobutyrate, t-butyl peroxy-3,5,5-trimethylhexanoate, t-butyl peroxybenzoate, 1,1-di-tert-butyl peroxy-3,5,5-trimethylcyclohexane, 1,1-di-tert-butyl peroxycyclohexane, 2,2-di(tert-butylperoxy)butane, bis(4-tert-butylcyclohexane)-1,2-di-tert-butylperoxy)butane, t-butyl peroxy-3,5,5-trimethylhexanoate, t-butyl peroxybenzoate, t-butyl peroxy-3,5,5-trimethylcyclohexane, t-butyl peroxy-1,2-di-tert-butylper ... One or a mixture of at least two of 2,4-di(tert-butylperoxy)pentyl peroxide, 2,5-dimethyl-2,5-di-tert-butylperoxyisopropylbenzene, 2,5-dimethyl-2,5-di-tert-butylperoxyisopropylbenzene, 2,5-dimethyl-2,5-di-tert-butylperoxyisopropylbenzene, diisopropylbenzene hydroperoxide, 2-ethylhexyl tert-butylperoxycarbonate, n-butyl 4,4-di(tert-butylperoxy)pentanoate, methyl ethyl ketone peroxide or cyclohexane peroxide; Preferably, the carbon-based free radical initiator is selected from one of 2,3-dimethyl-2,3-diphenylbutane, 2,3-dimethyl-2,3-di(4-methylphenyl)butane, 2,3-dimethyl-2,3-di(4-isopropylphenyl)butane, and 3,4-dimethyl-3,4-diphenylhexane, or a mixture of at least two thereof.
6. The adhesive layer resin composition according to any one of claims 1 to 5, characterized in that Based on 100 parts by weight of components (A) + (B), the amount of the initiator used is 0.1-5 parts by weight.
7. A glue-coated copper foil, characterized in that: The adhesive-coated copper foil comprises a copper foil layer and an adhesive layer covering the surface of the copper foil layer, and the adhesive layer is prepared from the adhesive layer resin composition according to any one of claims 1 to 6.
8. The adhesive-coated copper foil according to claim 7, characterized in that: The thickness of the adhesive layer is 3-7 μm; Preferably, the adhesive layer is applied to the matte surface of the copper foil; Preferably, the Rz of the rough surface of the copper foil is ≥5 μm.
9. A copper-clad laminate, characterized in that: The copper-clad laminate comprises a carbon-hydrogen bonding sheet and the above-mentioned adhesive-coated copper foil covering one side or both sides of the carbon-hydrogen bonding sheet.
10. A printed circuit board, characterized in that: The printed circuit board comprises the glue-coated copper foil as claimed in claim 7 and / or the copper-clad laminate as claimed in claim 9.
Citation Information
Patent Citations
A resin composition, a resin film, a circuit material, and a printed circuit board.
CN113072885B
Polybutadiene and epoxidized polybutadiene composition, adhesive, glued metal foil, prepreg, laminated board and preparation method
CN114479212A
Resin composition, circuit material containing same and printed circuit board
CN117924812A
Thermosetting resin composition, and resin varnish, prepreg and metal-clad laminate using the same
JP2011225639A
Resin composition, film and circuit board using the same
TWI582159B